Analysis of models for e-commerce adoption factors in developing countries - Hassen, Houache; Abd Rahim, Noor Hayani; Shah, Asadullah (IIUM Press, International Islamic University Malaysia, 2019)
Small and Medium-sized Enterprises (SMEs) have a considerable role in most developing countries because they are able to develop and improve the economy. Whereas e-commerce is also a vital subject in the field of research, where they offer significant benefits for these countries. However, the adoption of e-commerce in developing countries by SMEs is low due to several factors, including the lack of a suitable model for the adoption of e-commerce. Therefore, some of the most widely used models for the adoption of e-commerce in developing countries were highlighted, which were Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology (UTAUT) established by Molla and Licker (2005), Technology Organisation Environment (TOE) Integration of TOE and TAM, Perceived eReadiness Model (PERM) and E-commerce Success Factors. The exploratory research was conducted in this study. Finally, some recommendations were reached that may give the researchers a better understanding of the adoption of e-commerce in developing countries which they have not yet started using e-commerce.